Influence of Human Cord Blood Low-Molecular Fraction (below 5 kDa) on Morphological and Functional Characteristics of Erythrocytes after Hypothermic Storage - Zharkova, Yelena Ye.; Gulevsky, Aleksandr K. (Problems of Cryobiology and Cryomedicine, 2015)
N/A